(untitled) (Italian Review of Legal History, 2023)
This scientific article is dedicated to the peculiarities of legal differentiation in the border sphere in Ukraine. The article examines legislative and regulatory acts that have regulated the functioning of the border service during different periods of its existence. It also analyzes the process of its formation and development as an important component of Ukraine’s national and state security system. The article discusses its role in ensuring the protection of Ukraine’s state border. Additionally, an analysis of international experience in the field of protecting state borders of European countries has been conducted, which demonstrates the need for clearly defined priorities and appropriate strategies for the development of mechanisms for the protection and defense of shared state borders. The obtained results allowed us to establish that in the majority of European Union (EU) countries, the functions of border control are carried out by law enforcement agencies within the police force. In some countries, such as Malta (and partially in Spain), the control of maritime borders is entrusted to the armed forces. Several EU countries have specialized bodies or agencies (border services) that specifically deal with border-related issues outside the competence of the police. This applies to Finland, Latvia, Lithuania, the Netherlands, Poland, and Switzerland, where border guards have law enforcement powers in certain cases. Additionally, the national services responsible for external border control are often subordinate to various ministries, most of which are ministries of internal affairs, while in other countries, they also include the Ministry of Defense (France, Italy, Norway, Portugal, Spain, Sweden, and the Netherlands). International experience in safeguarding national borders in European countries emphasizes the importance of establishing clear priorities and development strategies for border protection and defense mechanisms. Over a significant period of time, international cooperation in this field has been evolving and actively implemented. Alongside the governing bodies of the European Union, key participants in this process are the border agencies of EU member states that share common borders. They operate based on bilateral and multilateral agreements on cooperation and mutual assistance in border-related matters, as well as international documents pertaining to border security. The article draws conclusions about positive changes in the legal status of the State Border Guard Service of Ukraine that have taken place over the past decade and examines the problems of legal differentiation in the border sphere in Ukraine due to russian aggression. In particular, due to fundamental differences between functions and tasks performed by the State Border Guard Service of Ukraine along different sections of Ukraine’s state border, as well as in connection with russian aggression, the idea of legal differentiation in the border sphere has been proposed. This would involve the creation of a separate military formation called the «Border Defense Forces» in the east and south of Ukraine, which would be integrated into the Armed Forces of Ukraine. In the western part of the country, the State Border Guard Service of Ukraine would remain under the Ministry of Internal Affairs of Ukraine, taking into account global experience in the protection, defense, and security of state borders by other countries.